Микола Макаренко — дослідник середньовічного стінопису - Коренюк, Ю. (Студії мистецтвознавчі, 2007)
The publication is dedicated to the memory of the noted Ukrainian scientist, archeologist, art critic and museum historian, defender of historic monuments.